PERFORMANCE AND EMISSION ANALYSIS OF HYDROGEN AND NATURAL GAS COFIRING IN COMBINED CYCLE GAS TURBINE POWER GENERATION - Sitanggang, Ruly (Journal of Applied Engineering Science, 2023)
The use of clean, abundant, and sustainable energy sources, such as solar and wind energy, is a strategy to reduce the reliance on fossil fuels and the danger of exposure to potentially harmful pollutants. However, increases in renewable energy utilisation might burden a power infrastructure due to its intermittent and variable characteristics. The intermittency of such renewables can be supported by a gas turbine power plant, especially if the gas turbines are fuelled with fuel that does not produce carbon emission. Using thermodynamic modelling software, this paper explains the technology and evaluates the performance of an existing natural gas fuelled CCGT plant in North Sumatera, Indonesia, if the facility is cofired with hydrogen. Hydrogen has a greater reactivity in comparison to natural gas, and related technological issues with hydrogen include faster flame speed, a higher adiabatic flame temperature, shorter autoignition delay periods, a broader flammability range, and increased volumetric fuel flow rate. Thermodynamic modelling demonstrates that plant production increases with the addition of H2 to the cofiring mixture, but CO2 emissions decrease.